Catalytic gasification of empty palm fruit bunches using charcoal and bismuth oxide for syngas production - Monir, Minhaj Uddin; Abd Aziz, Azrina; Md. Rezaul Karim, Kaykobad; Khatun, Fatema; Tarek, Mostafa; Yousuf, Abu; Vo, Dai-Viet N. (Springer-Verlag, 2022)
The purpose of this research is to evaluate the intent of empty fruit bunches of palm oil (EFBpalm oil) to catalytic gasification of wood produced charcoal (Woodcharcoal) in order to notify the large-scale application of Woodcharcoal as a possible gasification feedstock. In this study, co-catalyst of bismuth oxide (Bi2O3) was also used to obtain syngas. The raw samples were characterized by proximate and ultimate analyses, X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) analyses. The produced syngas was analyzed by online portable gas analyzer and gas chromatography-thermal conductivity detector (GC-TCD). The syngas composition of H2 increased from 3.91 to 4.70% (increased 20.20%), CO increased from 5.73 to 6.30% (increased 10.53%), whereas CO2 decreased from 20.60 to 12.67% (decreased 38.50%) and CH4 concentration increased insignificantly from 0.35 to 0.37% (increased 5.7%) which was happened due to the use of WoodCharcoal and Bi2O3 with EFBpalm oil during gasification. According to the findings, carbon is abundant in WoodCharcoal, which may considerably boost the gasification reactivity with Bi2O3. The yield of syngas (H2 and CO) increased when WoodCharcoal and Bi2O3 were used instead of single EFBppo gasification, indicating that catalyst (WoodCharcoal) and co-catalyst (Bi2O3) have a high potential for thermal decomposition and dehydrogenation of volatile matter. Therefore, catalytic gasification of empty palm fruit bunches will be the prospective energy sources for the production of syngas with the utilization of WoodCharcoal and Bi2O3.